2014
DOI: 10.1038/labinvest.2014.111
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of protease nexin-1 in fibroblasts during idiopathic pulmonary fibrosis regulates thrombin activity and fibronectin expression

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic diffuse lung disease characterized by an accumulation of excess fibrous material in the lung. Protease nexin-1 (PN-1) is a tissue serpin produced by many cell types, including lung fibroblasts. PN-1 is capable of regulating proteases of both coagulation and fibrinolysis systems, by inhibiting, respectively, thrombin and plasminergic enzymes. PN-1 is thus a good candidate for regulating tissue remodeling occurring during IPF. We demonstrated a significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
17
1
Order By: Relevance
“…Secondly, serpinE2 is the phylogenetically closest relative of Plasminogen activator inhibitor type 1 (PAI-1)15 that is implicated in the pathology of fibrosis in multiple organs including the heart, lung, kidney, liver and skin16 SerpinE2 is an inhibitor of uPA and tissue plasminogen activator but has a larger inhibition spectrum than PAI-1, and it may also modulate extracellular matrix degradation in vascular cell10. SerpinE2 is thought to have a pathogenic role in the development of another fibrotic disease, and scleroderma36.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, serpinE2 is the phylogenetically closest relative of Plasminogen activator inhibitor type 1 (PAI-1)15 that is implicated in the pathology of fibrosis in multiple organs including the heart, lung, kidney, liver and skin16 SerpinE2 is an inhibitor of uPA and tissue plasminogen activator but has a larger inhibition spectrum than PAI-1, and it may also modulate extracellular matrix degradation in vascular cell10. SerpinE2 is thought to have a pathogenic role in the development of another fibrotic disease, and scleroderma36.…”
Section: Discussionmentioning
confidence: 99%
“…In the cartilage of OA patients, there is a significant increase in the level of serine protease Htra1 (high temperature factor A-1), which mediates proteolysis of aggrecan and contributes to OA pathology 41 42 . Initially, PN-1 was identified as a serine protease inhibitor in cartilage anlagen during embryogenesis, and interacted with both ECM and intracellular cartilage components 30 43 44 , which is consistent with its role in the binding and inactivation of extracellular proteases followed by internalization 45 . The activity of PN-1 is regulated by several matrix components, such as FN 46 , collagen II, and collagen I 47 .…”
Section: Discussionmentioning
confidence: 70%
“…There has been a general academia consensus in that FN is widely present non-collagen glycoprotein with numerous biological functions. Recent studies have observed considerably enhanced FN formation as well as upregulation of fibroblasts mitosis and proliferation in cases of pulmonary fibrosis (30). E-cadherin (CDH1) belongs to family of cadherin, which is a typical epithelial cell surface marker.…”
Section: Discussionmentioning
confidence: 99%